Organic chemistry - Bruice, Paula Yurkanis , 1941- (Boston, Massachusetts : Prentice Hall, 2011)
New edition of an organic chemistry text that encourages students to think about what they have already learned and then apply this knowledge in a new setting. Bruice (U. of California) has organized the material in a way that discourages rote memorization. Functional groups are organized around mechanistic similarities such as electrophilic and nucleophilic additions; radical, nucleophilic, electrophilic aromatic, and nucleophilic acyl substitutions; and eliminations. The 30 chapters discuss introductory material; hydrocarbons, stereochemistry, and resonance; substitution and elimination reactions; identification of organic compounds; aromatic, carbonyl, and bioorganic compounds; and special topics. Includes some short biographies of scientists, together with a b&w photograph, and color illustrations and diagrams. Annotation c. Book News, Inc., Portland, OR (booknews.com)